Development of LMS-Based E-Learning for Physical Education Learning in Binjai City - Ningsih, Sri Wahyuni Retno; Dewi, Rahma; Irfan, M. (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2025)
This study aims to develop an LMS-based e-learning product for PJOK learning in Binjai City. This study aims to develop an LMS-based e-learning product for PJOK learning in Binjai City. The methodology used is research and development. The sample was selected using total sampling, comprising 50 seventh-grade students from SMPN 1 Binjai's class VII. The results of the study on a small-scale trial of the level of feasibility of the learning application product 4.4 out of 5.0 are included in the "outstanding" category, which, when converted to a value for product feasibility, the product that has been tested on a small scale is declared "feasible" for use. The results of a large-scale trial of the level of feasibility of the LMS-Based E-Learning Product product are 4.4 out of 5.0, included in the "excellent" category, which, when converted to a product feasibility value, the product that has been tested in the field test is declared "feasible" to be used as an application in the implementation of physical education, sports and health learning (PJOK). The conclusion drawn from the results of both small-scale and large-scale trials in this study falls into the excellent category, indicating that the product developed by the researcher can be utilized as a solution for teaching PJOK learning based on E-Learning principles.